The elements of organic gardening - Charles (Kales Press, 2007)
The Elements of organic gardening is a practical guide to organic gardening as practiced at Highgrove and The Prince of Wales’s two other gardens: Clarence House in London and Birkhall in Scotland"--Provided by publisher.